The Relationship of Literacy Skills to the Misconception of Science Teaching for Madrasah Ibtidaiyah Teacher Candidates - fitriani, hijriah (SEARCH: Science Education Research Journal, 2024)
Literacy is a serious problem in the world of Indonesian education. According to data from the World's Most Literate Countries 2016 conducted by Central Connecticut State University, Indonesia ranks 60th in terms of literacy among the 61 countries surveyed. Indonesia has six core literacy competencies. Namely numeracy literacy, digital literacy, financial literacy, cultural literacy, as well as civic literacy and science literacy. Indonesia's science literacy is ranked 9th from the bottom or 71st based on the latest mapping of the Program for International Students Assessment (PISA) in 2018. Namely with an average score of 396. Still lower than the ideal value of 500. Meanwhile, in 2022, science literacy increased by 6 positions from the previous position and is Indonesia's highest position while participating in PISA. Science literacy has a relatively long history and is widely used in science education at various levels of education. Science literacy is defined as the ability to understand scientific processes and obtain meaningful scientific information that can be used in daily life. Misconceptions can occur due to several factors such as lack of teacher knowledge, students' interest in learning, students' way of thinking and teachers, and others. Misconceptions often occur in science material that is abstract or requires visual explanation in its understanding so that students find it difficult to understand, prospective teachers also have difficulty teaching the material. Science education or science is a science that makes students have the ability to think critically, logically and creatively. Natural sciences (science) are necessary for all individuals and all citizens at different levels, in education also requires knowledge, understanding, and skills in science or science. This study is a quantitative research, namely research related to numbers, with a correlational study approach, namely the researcher only analyzes the relationship between variables without determining cause and effect. This study aims to determine the relationship between literacy skills and misconceptions of science teaching in prospective MI teachers. the population in this study is Madrasah Ibtidayah Teacher Candidate Students at IAIN Sorong, the population is the sum of all variables to be studied, with a sample of 23 PGMI semester 6 students, data collection methods using questionnaires about the literacy skills of prospective teachers and also misconceptions according to prospective teachers.